Columbia University Master of Public Health Core Curriculum: Implementation, Student Experience, and Learning Outcomes, 2013-2018. (January 2022) - Garbers, Samantha; March, Dana; Kornfeld, Julie; Baumgartner, Sabrina R.; Wiggin, Maggie; Westley, Lauren A.; Ballesteros-Gonzalez, Diana; Delva, Marlyn; Fried, Linda P.
Objectives: Public health education must respond to 21st-century public health challenges in an ever-evolving landscape. We describe implementation and educational outcomes of the Columbia University Master of Public Health (MPH) Core (hereinafter, Core) curriculum since its inception. Methods: This retrospective evaluation combined 6 years (2013-2018) of student survey data collected from students (N = 1902) on the structure and delivery of the Core curriculum to quantify implementation, student experience, and learning outcomes, both during study (Core Evaluation Survey [CES]) and after graduation (Graduate Exit Survey [GES]). We used χ 2 tests and analysis of variance to compare outcomes across years, and we used McNemar tests to compare differences in outcomes from the same students at different time points. Results: Of 1902 respondents to the CES, 1795 (94.4%) completed the Core curriculum. During the study period, 81.7% of students were able to integrate concepts across Core curriculum modules with ease; postgraduation, a similar proportion of respondents were able to apply Core curriculum content to departmental and certificate coursework and applied field experiences. On-time graduation rates were high (range, 85%-93%). Conclusions: The high percentage of students who reported their ability to integrate concepts and who completed the Core during the study period likely reflected changes to teaching team structures, training, attention to inclusion and equity, and collaboration to implement active learning strategies. The Core curriculum meets its intended goals by providing critical learning abilities to support ongoing interdisciplinary work.